Knowledge, innovation and space - Karlsson, Charlie 1945- (Edward Elgar Pub. Ltd, 2014)
This volume extends our understanding of the many different ways in which distance impacts the knowledge conversion process. While addressing different facets of knowledge, innovation and space, the authors provide an overview of relevant topics in contemporary research concerned with the global, national, regional and local dynamics of knowledge and innovation. Knowledge itself is a raw input into the innovation process, which can then transform it into an economically useful output such as a prototype, patent, licence or new firm. New knowledge is often tacit and thus tends to be highly localized, as indeed is the conversion process. Consequently, as the book demonstrates, space or distance matter significantly in the transformation of raw knowledge into beneficial knowledge. This innovative book will appeal to academics, students and researchers in the fields of regional science, economics, sociology and innovation. It will also be of interest to policymakers and consultants in international organizations, in particular those dealing with entrepreneurship, development, R&D policies and regional policies on different spatial scales
Keywords: Innovation; Wissensintensives Unternehmen; Regionalentwicklung; Spill-over-Effekt; Kioto <2008>; Knowledge, Theory of; Technological innovations; Knowledge management; Electronic books